Intonation Analysis of The Movie: Fall from Grace - Hussein, Abdullah Uday; Mansour, Rafida (Al-Adab Journal, 2022)
Language has really changed in many aspects through the past hundred years or so. There are many factors due to which this transformation is seen in the present-day life in comparison with the more distant life; the modernization of the lives of the individuals as well as the communities around the globe, the invention of advanced technology in all fields of science, the awakening scientific discoveries and the rapidity of life has brought upon some coarse changes in languages, especially in English language. The purpose of this research is to know whether the language has really changed in terms of intonation throughout a few decades or not. For this purpose, some scenes from the modern movie have been taken into consideration. The analysis of the data has paved way for tremendous results and outcomes in the attitudinal function of intonation in the modern-day English that have been illustrated in both tabular and graphic form. This study definitively answered the question regarding changes in the intonation in English language through the past century.